Algorithmic Ethics and Qur'anic Tabayyun: Knowledge Authority and AI Bias in the Digital Age - Fepriani, Jumarni; Ratnasari, Dwi (QiST: Journal of Quran and Tafseer Studies, 2026)
The development of artificial intelligence (AI) and digital algorithms has significantly changed the way knowledge is produced, distributed, and legitimized in the digital era. This situation raises ethical and epistemological challenges, particularly in religious contexts, where the truth and authority of information have a strong moral dimension. This study aims to formulate an integration between the principle of Qur'anic tabayyun with the concept of algorithmic ethics to build a more critical, transparent, and responsible approach to the use of AI. This study uses a literature study approach by analyzing scientific articles obtained through the Publish or Perish and Elsevier databases, with a publication range of 2015-2026. The analysis process was carried out through the stages of identification, selection, and synthesis of research relevant to the focus of the study. The results show that the integration of the concept of Qur'anic tabayyun into the algorithmic ethics framework is relevant to ensure the process of verification, caution, and responsibility in the management of information generated by AI. This research is expected to provide a conceptual contribution to the development of a technology ethics framework based on Qur'anic values while enriching the discourse on the transformation of the authority of religious knowledge in the era of artificial intelligence.